Pengolahan Mie Kering Tersubstitusi Tepung Mangrove Sebagai Diversifikasi Produk UMKM SOMANO Surabaya di Masa Pandemi Covid-19 : Pengolahan Mie Kering Tersubstitusi Tepung Mangrove - Ulya Sarofa; Luqman Agung Wicaksono (Universitas Nahdlatul Ulama Sidoarjo, 2021)
SOMANO MSMEs are MSMEs (Micro, Small and) Medium Enterprises) engaged in food and beverages made from mangrove fruit (Sonneratia caseolaris). SOMANO MSMEs are very potential because they are located close to the location of Mangrove Ecotourism Surabaya. However, the covid-19 pandemic has an impact on the declining number of Mangrove ecotourism tourists, which also led to a decrease in sales of SOMANO MSMEs. During this time MSMEs SOMANO is more focused on making liquid mangrove processed in the form of mangrove syrup. To increase sales during the covid-19 pandemic, it is necessary to diversify products, especially healthy functional products that can generally improve health. Mangrove flour has a high enough dietary fiber component that can improve digestive health which indirectly can also increase the body's overall immunity. Mangrove flour-subtitling dry noodle products were chosen as diversification of SOMANO MSME products, because previously these MSMEs did not have the type of products in the form of dry noodles. In addition, dry noodles are a type of food that is quite popular by the people of Indonesia so that it is expected to boost the sales of SOMANO MSMEs during the Covid-19 Pandemic. Therefore, it is considered necessary to carry out PIHAT community service program (Grant application of research results for the community) based on innovation of mangrove flour processed products as product diversification. The purpose of PIHAT community service activities is: increasing the knowledge and skills of SOMANO MSMEs, especially their owners and employees in processing mangrove flour into dry noodle processed products and introducing good ways of packaging and marketing products so as to increase product sales. The methods that will be used are extension and training on processing dried noodles substituted mangrove flour and packaging and marketing. At the end of the training activity, donated tools in the form of noodle makers and food cabinet dryers that are expected to help MSME owners in producing mangrove noodles.